Phenotypic and genotypic characterisation of root nodule bacteria nodulating Millettia pinnata (L.) Panigrahi, a biodiesel tree - Arpiwi, Ni; Yan, Guijun; Barbour, Elizabeth; Plummer, Julie; Watkin, Elizabeth (Springer, 2012)
Aims. Milletia pinnata is a leguminous tropical tree that produces seed oil suitable for biodiesel and is targeted to be planted on marginal land associated with nitrogen poor soil. This study aimed to identify effective rhizobia species for M. pinnata. Methods. Soil samples were collected from M. pinnata grown in Kununurra, Australia. Rhizobia were trapped, characterised and sequenced for 16S rRNA, atpD, dnaK and recA genes. Results. Forty isolates tolerated pH 7 – 9, temperatures 29 – 37 °C, salinity below 1 % NaCl, and had optimal growth on mannitol, arabinose or glutamate as a single carbon source, a few grew on sucrose and none grew on lactose. Inoculation of isolates increased shoot dry weight of M. pinnata’s seedlings in nitrogen minus media. Slow-growing isolates were closely related to Bradyrhizobium yuanmingense, Bradyrhizobium sp. DOA10, Bradyrhizobium sp. ORS305 and B. liaoningense LMG 18230T. The fast-growing isolates related to Rhizobium sp. 8211, R. miluonense CCBAU 41251T, R miluonense CC-B-L1, Rhizobium sp. CCBAU 51330 and Rhizobium sp. 43015. Conclusions. Millettia pinnata was effectively nodulated by slow-growing isolates related to Bradyrhizobium yuanmingense, Bradyrhizobium sp. DOA10 Bradyrhizobium sp. ORS305, B. liaoningense LMG 18230T and fast-growing isolates related Rhizobium sp. 8211, R. miluonense, Rhizobium sp. CCBAU 51330 and Rhizobium sp. 43015.